Development of multistakeholder scenarios of secondary forest management: a multiagent system simulation approach - Purnomo, H.; Priyadi, H.; Yasmi, Yurdi; Yuliani, L.; Prabhu, Ravi (Gadjah Mada University and Kansai Environmental Engineering Centre, 2002)
The state owned company, PT. Inhutani II Sub Unit Malinau, has managed the lowland dipterocarps forest in Malinau District, East Kalimantan for over 10 years. They established permanent sample plots (PSP) for measuring the growth and the yield in their area. However, current regulations do not give the company a sufficient space to use the PSP data for managing the area, nor a systematic way to involve the communities in the management of the forest. This research was aimed to seek scenarios of sustainable secondary forest management. The scenarios were developed through simulation of social and biophysical components in the area using Multi-Agent System (MAS). MAS is a branch of artificial intelligent for creating artificial society used for social simulation. This paper presents scenarios' development process and scenarios of collaborative management of the forest. The results reveal that Multi-Agent System (MAS) is a powerful tool in simulating and in developing scenarios of sustainable dipterocarps forest management. the sustainability was measured by indicators of forest cover and standing stock, carbon stock, communities incomes, the company revenue and taxes paid to the local and center governments. It was also found that collaboration between PT. Inhutani II and the communitie appeared to be the most suitable alternative for sustainable secondary dipterocarps forest management.